Histological Characteristics of Altered Human Lingual Frenulum - de Castro Martinelli, Roberta Lopes; Marchesan, Irene Queiroz; Gusmão, Reinaldo Jordão; de Castro Rodrigues, Antonio; Berretin-Felix , Giédre (International Journal of Pediatrics and Child Health, 2014)
Aim: The aim of this study was to describe the histological characteristics of altered human lingual frenulum. Materials and Methods: Between March and July, 2011, 50 children between 6 months and 4 years of age were assessed by a Speech Language Pathologist in a Public Health Care Service in Brotas – Sao Paulo, Brazil. The lingual frenulum evaluation protocol proposed by Marchesan (2010, 2012) was administered to the 50 children – 26 male and 24 female. Of the 50, 8 children had lingual frenulum alterations. The 8 children with lingual frenulum alteration underwent lingual frenectomy. The materials for analyses were taken from 7-micrometer-thick tissues sections. Staining was employed using haematoxylin paired with eosin (H&E), Masson’s trichrome and picrosirius red. Results: The assessment of the lingual frenulum indicated that 8 children had lingual frenulum alteration. Surgery was performed and the material collected was submitted to analyses. The histological analyses demonstrated that the lingual frenulum of children with ankyloglossia or with short frenulum had bundles of striated skeletal muscle fibers, high frequency of type I collagen in the deep layers and compact bundles of elastic fibers positioned near the epithelial lining. Bundles of muscle fibers were not observed in anterior frenulum and short frenulum with anterior fixation. Type I collagen and bundles of elastic fibers sparse and far from the epithelial lining were observed in those types of frenulum. Conclusion: The analysis of the histological sections demonstrated the characteristics of altered human lingual frenulum.